A systematic review insights on integrating augmented reality into surgical training & clinical practice surgery - Ismail, Muchammad; Baroroh, Dawi Karomati; Agarwal, Aanchal (OPSI, 2025)
Augmented Reality (AR) is increasingly recognized as a key enabler of future healthcare innovation, particularly in advancing medical education, clinical training, and surgical procedures. This study presents a Systematic Literature Review (SLR) of AR integration in the medical domain, analysing 62 peer-reviewed articles from the Scopus database. The review explores five aspects: interaction devices, AR functions, AR impacts, solution validation methods, and medical implementation stages. Results reveal that appearance is the most dominant AR function (41%), followed by procedural guidance in both training and real clinical settings (24% each). Head-Mounted Displays (HMDs) are the most widely used interaction device (67%), offering immersive and real-time visual support. AR integration is most prevalent during the intra-operative phase (44%). Reported AR impacts commonly span multiple dimensions, including enhanced accuracy, effectiveness, efficiency, error, and educational outcomes (37%). Validation methods are primarily based on statistical analysis (40%). This review underscores AR’s growing role in transforming healthcare delivery, medical education, and highlights opportunities for future development in multifunctional AR systems, cost-benefit analyses, and expansion into additional medical subspecialties.